Fluidized bed roasting technology in iron ores dressing in China — A review on equipment development and application prospect - Tang, Zhidong; Gao, Peng; Han, Yuexin; Guo, Wang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Due to the undesirable characteristics of iron ore resources in China, they are refractory to utilize with high efficiency. The mining and mineral processing costs are usually high. The supply of domestic iron ores of China has been in serious shortage for a long time. Therefore, the development and utilization of complex and refractory iron ore resources are extremely urgent. Magnetizing roasting followed by magnetic separation is an important method for the beneficiation of low grade iron ores. More attention has been paid to fluidized bed magnetizating roasting rather than shaft furnace and rotary kiln roasting in recent years. In this paper, the main characteristics of fluidized bed magnetizating roasting technology and the development process of its application in the beneficiation of refractory iron ores are introduced. The research status of several typical fluidized bed roasting processes and equipment in China are also summarized. Moreover, the application prospect of the technology for efficient utilization of low grade hematite, siderite, limonite ores and iron containing tailings is analyzed.